2003
DOI: 10.1038/sj.npp.1300238
|View full text |Cite
|
Sign up to set email alerts
|

Group II mGlu Receptor Activation Suppresses Norepinephrine Release in the Ventral Hippocampus and Locomotor Responses to Acute Ketamine Challenge

Abstract: Group II mGlu receptor agonists (eg LY379268 and LY354740) have been shown to reverse many of the behavioral responses to PCP as well as glutamate release elicited by PCP and ketamine. In the present set of experiments, we used in vivo microdialysis to show that, in addition to reversing PCP-and ketamine-evoked glutamate release, group II mGlu receptor stimulation also prevents ketamine-evoked norepinephrine (NE) release. Pretreating animals with the mixed 2/3 metabotropic glutamate (mGlu2/3) receptor agonist … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
72
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(77 citation statements)
references
References 45 publications
5
72
0
Order By: Relevance
“…142 Finally, these drugs reverse ketamine-induced stimulation of ventral hippocampal norepinephrine release, which may also be linked to prefrontal hyperglutamatergia. 143 In contrast to its effects on glutamate, group II agonists do not inhibit, 90 and may enhance, 134 NMDAR antagonist effects on PFC DA release, suggesting a dissociation in the regulation of prefrontal glutamate and dopamine systems. Group II agonists also do not reverse PCP-induced behavioral sensitization, 141 PCP-or apomorphine-induced disruption of PPI, 144 or MK-801-induced disruption in delayed alternation.…”
Section: Metabotropic Receptorsmentioning
confidence: 99%
“…142 Finally, these drugs reverse ketamine-induced stimulation of ventral hippocampal norepinephrine release, which may also be linked to prefrontal hyperglutamatergia. 143 In contrast to its effects on glutamate, group II agonists do not inhibit, 90 and may enhance, 134 NMDAR antagonist effects on PFC DA release, suggesting a dissociation in the regulation of prefrontal glutamate and dopamine systems. Group II agonists also do not reverse PCP-induced behavioral sensitization, 141 PCP-or apomorphine-induced disruption of PPI, 144 or MK-801-induced disruption in delayed alternation.…”
Section: Metabotropic Receptorsmentioning
confidence: 99%
“…Both PCP and ketamine dramatically increase noradrenaline release and turnover in brain (Bowers and Morton, 1994;Deutch et al, 1987;Kubota et al, 1999a;Lorrain et al, 2003;Rasmussen et al, 1991). In a recent study, Harkin et al (2001) demonstrated that the potent alpha-2 agonist, clonidine, strongly attenuated NMDA antagonist-induced hyperlocomotion in mice, while the potent alpha-2 receptor antagonist, yohimbine, produced opposite effects; Swanson and Schoepp (2003)reported similar effects of clonidine in rats.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, highly selective mGlu2 receptor allosteric potentiators have been developed (Johnson et al, 2003;Lorrain et al, 2003b;Schaffhauser et al, 2003;Pinkerton et al, 2004). These small molecules do not activate the mGlu2 receptor directly but act at an allosteric site on the receptor to potentiate glutamateinduced activation of the receptor (Schaffhauser et al, 2003).…”
mentioning
confidence: 99%